Contamination of microplastic in bivalve: first evaluation in Vietnam - Nam, Phuong Ngoc; Tuan, Pham Quoc; Thuy, Duong Thi; Quynh, Le Thi Phuong; Amiard, Frederic (Vietnam Journal of Earth Sciences, 2019)
Microplastics (MP) are omnipresent in ecosystems. Some studies focus on MP fates and their toxicology on biota for the last ten years in the world. In the present study, MP was identified in bivalve (Perna Viridis) collected in Vietnam for the first time using micro-Fourier transform infrared Microspectroscopy (µFTIR) technique. Organisms were digested by KOH 10% solution then separated using KI 50% solution. The average concentration evaluated at 2.60 MP/individual and 0.29 MP/gram of wet tissue. Six types of MP were found with a high proportion of polypropylene (PP) (31%) and polyester (23%). MP characterizations were also observed which bring to much important information such as the source of MP contamination in bivalve from Vietnam. Nevertheless, more work needs to be invested in the future such as on different species or environment compartments which permit to the global view of MP contamination in Vietnam